Cocaine induced first-degree and high-grade second-degree atrioventricular block in a dog: a case report - Johnson, Jake; Bowden, Seth; Fitzgerald, Alyson H.; Enders, Brittany D.; Pierce, Kursten V. (Frontiers in Veterinary Science, 2025)
BackgroundCommon cocaine-induced arrhythmias include tachyarrhythmias such as sinus tachycardia, supraventricular tachycardia, and atrial fibrillation. Most studies evaluating cocaine toxicosis in canines have been performed in an experimental setting, using intravenous administration of the drug. Though helpful, these studies cannot be directly extrapolated in a clinical setting given the different routes of administration.Case detailsA 2-year-old male-neutered Chihuahua presented for further management of acute onset of lethargy and a transient episode of unresponsiveness. Initial point of care ECG was consistent with an underlying sinus bradycardia with concurrent first-degree AV block and intermittent high-grade second-degree AV block. No murmur was noted on thoracic auscultation. Normal sinus rhythm returned after administration of atropine and epinephrine. Upon referral to a different facility for pacemaker implantation, sinus tachycardia was appreciated on point of care ECG without evidence of supraventricular or ventricular ectopy. On cardiac focused point of care ultrasound there was normal heart function and structure with no evidence of congenital heart defects. Both cardiac troponin and NT-proBNP were within normal limits. Urine toxicology was positive for cocaine, cocaine metabolites, norfentanyl and trace amounts of fentanyl. The patient was hospitalized overnight on telemetry, during which time infrequent ventricular premature complexes were the only abnormalities noted. The patient was discharged the following day.ConclusionCocaine-induced AV block in canines is an unusual presentation in a clinical setting, given the sympathetic stimulation this drug commonly causes. Emergency veterinary clinicians should be aware of this rare but important electrocardiographic abnormality following cocaine toxicosis.